Pembelajaran Bahasa Arab Bagi Non Muslim Berbasis Moderasi Beragama di Sekolah Umum - Nurul Hidayah; Ludfi Muyassaroh (Peneliti.net, 2023)
Arabic language learning is generally only studied by Muslim students, but in reality there are several public schools that have included this subject in their school curriculum, this situation needs special attention, considering that Arabic is closely related to hijaiyah letters which are not known to non-Muslim students. For this reason, this study used interviews, documentation and observation in collecting data in the field, the researchers also checked the validity of the data through a triangulation process. This study shows that the objectives of learning Arabic for non-Muslims are almost the same as learning for Muslim students, but there is an emphasis on recognizing hijaiyah letters and pronunciation and pouring them in written form in the form of words to sentences.The material is determined by the teacher and adapted to the daily context of the students. The evaluation is in the form of oral, namely the pronunciation of a few words and simple conversations as well as a writing test by assembling letters into words and sentences. Learning Arabic at this school has met the principles of moderation, namely universal, balanced, integrated and has the principle of diversity, but still needs to be improved, especially in terms of methods and media, which must always be upgraded by the teacher, so that the universality of a language can be felt when non-Muslim students learn. So far, Arabic has only been considered to be understood and actually used by Muslim students in various educational institutions